Sonolysis in Prevention of Brain Infarction During Cardiac Surgery (SONORESCUE): Randomized, Controlled Trial - Školoudík, David; Hurtíková, Eva; Brát, Radim; Herzig, Roman; SONORESCUE Trial Group (Medicine, 2016)
Here, we examined whether intraoperative sonolysis can alter the risk of new ischemic lesions in the insonated brain artery territory during coronary artery bypass grafting (CABG) or valve surgery.Silent brain ischemic lesions could be detected in as many as two-thirds of patients after CABG or valve surgery.Patients indicated for CABG or valve surgery were allocated randomly to sonolysis (60 patients, 37 males; mean age, 65.3 years) of the right middle cerebral artery (MCA) during cardiac surgery and control group (60 patients, 37 males; mean age, 65.3 years). Neurologic examination, cognitive function tests, and brain magnetic resonance imaging (MRI) were conducted before intervention as well as 24 to 72 hours and 30 days after surgery.New ischemic lesions on control diffusion-weighted MRI in the insonated MCA territory ≥0.5 mL were significantly less frequent in the sonolysis group than in the control group (13.3% vs 26.7%, P = 0.109). The sonolysis group exhibited significantly reduced median volume of new brain ischemic lesions (P = 0.026). Stenosis of the internal carotid artery ≥50% and smoking were independent predictors of new brain ischemic lesions ≥0.5 mL (odds ratio = 5.685 [1.272-25.409], P = 0.023 and 4.698 [1.092-20.208], P = 0.038, respectively). Stroke or transient ischemic attack occurred only in 2 control patients (P = 0.496). No significant differences were found in scores for postintervention cognitive tests (P > 0.05).This study provides class-II evidence that sonolysis during CABG or valve surgery reduces the risk of larger, new ischemic lesions in the brain.www.clinicaltrials.gov (NCT01591018).
Keywords: koronární bypass; Male; ultrazvuková terapie; difuzní magnetická rezonance; kognitivní dysfunkce; Ultrasonic Therapy; Coronary Artery Bypass; Intraoperative Complications; Aged; Prospective Studies; mužské pohlaví; senioři; Cognitive Dysfunction; Neuroimaging; Brain Infarction; mozkový infarkt; peroperační komplikace; Neuropsychological Tests; neurozobrazování; lidé; ženské pohlaví; Diffusion Magnetic Resonance Imaging; arteria cerebri media; Humans; ultrasonografie dopplerovská; neuropsychologické testy; Female; Ultrasonography, Doppler; lidé středního věku; Middle Cerebral Artery; Middle Aged; prospektivní studie